Implementation of the accelerated algorithms for integer division in the FPGA - Опанасенко, В. Н.; Лисовый, А. Н.; Сорока, Е. В. (Problems of Informatization and Control, 2008)
The structural division of the implementation of the modules in the elemental basis of FPGA type FPGA, made ​​by behavioral algorithms description language VHDL. Implemented check the functioning of the modules division simulation system ModelSim Xilinx Edition - MXE III with a test stand